2021
DOI: 10.7554/elife.65663
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic Bordetella pertussis infections in a longitudinal cohort of young African infants and their mothers

Abstract: Recent pertussis resurgence in numerous countries may be driven by asymptomatic infections. Most pertussis surveillance studies are cross-sectional and cannot distinguish asymptomatic from pre-symptomatic infections. Longitudinal surveillance could overcome this barrier, providing more information about the true burden of pertussis at the population level. Here we analyze 17,442 nasopharyngeal samples from a longitudinal cohort of 1320 Zambian mother/infant pairs. Our analysis has two elements. First, we demon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 58 publications
2
24
0
Order By: Relevance
“…However, Ct is a continuous variable, and the selection of any Ct cut point is arbitrary and hence controversial. 19 We further note that most COVID-19 surveillance studies assess individuals who are acutely ill when viral loads, and hence PCR signals, are likely at peak intensity. By contrast, the population in this study were tested after they had died.…”
Section: Methodsmentioning
confidence: 90%
“…However, Ct is a continuous variable, and the selection of any Ct cut point is arbitrary and hence controversial. 19 We further note that most COVID-19 surveillance studies assess individuals who are acutely ill when viral loads, and hence PCR signals, are likely at peak intensity. By contrast, the population in this study were tested after they had died.…”
Section: Methodsmentioning
confidence: 90%
“…Postmortem descriptions of lung pathology in 8 human infants who died from infantile pertussis revealed marked leukocytosis and pulmonary hypertension (37), features replicated in mouse and baboon pneumonic models (36,38,39), suggesting that these conventional pneumonic infection models reasonably replicate the most extreme form of human disease. However, these cases are extreme; pertussis generally is described as a disease of the upper respiratory tract that induces relatively little inflammation and histopathology (40,41) and often could occur with minimal symptoms and go undiagnosed (25). B. pertussis is highly infectious to humans, indicating that small numbers of bacteria landing in the upper respiratory tract can efficiently colonize, grow, and spread.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, these aspects of early infection are most relevant to the current challenge of the ongoing circulation of B. pertussis. Indeed, recent work has revealed that a large proportion of human infections are asymptomatic and undiagnosed (25). Assays that specifically measure how colonization, early growth, and immunomodulation contribute to shedding and transmission during the catarrhal stage of infection, before and perhaps independent of lower respiratory tract infection, are critical for development of vaccines that can prevent transmission.…”
Section: Modeling Immune Evasion and Vaccine Limitations By Targeted Nasopharyngeal Bordetella Pertussis Inoculation In Micementioning
confidence: 99%
“…Among all these reasons, the inefficient protection afforded by current aP vaccines may be the major issue for the insufficient prevention and control of whooping cough. Several studies have suggested that current aP vaccines cannot prevent B. pertussi s infection and transmission because they induce only humoral immune responses but not efficient cellular and mucosal immune responses ( 8 10 ). The current intramuscular acellular pertussis (aP) vaccines elicit strong antibody and Th2-biased responses but not necessary cellular and mucosal immunity.…”
Section: Introductionmentioning
confidence: 99%